The effects of x-rays (radiation) on embryonic and fetal during developmental pregnancy stages - Musa Garba, Abdullahi; Mohd Ekhwan, Toriman (2015)
Preconception irradiation of either parent’s gonads has not result in increased cancer or malformation in their children. The radiation dose and gestational ages during X-rays is the yard stick for measuring whether it will have an effect on the embryo or foetus at the time of exposure. During X-rays, high dose of ionizing radiation on embryo or foetus may causes some effects such as miscarriage, restriction of fetal growth, congenital malformation (which include microcephaly), or lead to mental retardation sometimes can cause cancer during childhood. The experimental observation showed that, radiation-induced of 100mGy equal to 10rads, may usually result to death of the embryo that may kill up to 20% of human embryos or fetuses. The radiation-induced of 5000 mGy equivalent to 500 rads also kill 100% of human embryos or fetuses before 18 weeks gestation. Therefore, it is recommended that during pregnancy or developmental stages X-rays of high dose is not advisable.